Two visual working memory representations simultaneously control attention - Yanan Chen; Feng Du (Scientific Reports, 2017)
Abstract It has been proposed that only one visual working memory (VWM) representation can be activated to influence perception directly, whereas other VWM representations are accessory items which have little influence on visual selection. The sole active VWM representation might reflect a fundamental bottleneck in the information processing of human beings. However, the present study showed that each of two VWM representations can capture attention and interfere with concurrent visual search. In addition, each of two VWM representations can interfere with concurrent visual search as much as can a single cued VWM representation. Moreover, when two memory-matching distractors appear in visual search, two VWM representations produce a larger memory-driven capture effect than a single memory-matching distractor. Thus, two VWM representations can simultaneously control attention.